Choosing Methods of Conflict Resolution: Is Individualism-Collectivism the Key? - Gire, Targema James (My University, 1993)
Researchers examining the influence of the individualism-collectivism value dimension on procedural preferences for conflict resolution (e.g., Leung, 1987; Leung, Bond, Carment, Krishnan, & Liebrand, 1990; Leung & Lind, 1986) have suggested that people from individualistic societies tend to prefer adversarial procedures such as arbitration, while collectivist persons tend to prefer bargaining and mediation. However, almost all of these collectivistic samples were drawn from Oriental societies where some unique values such as the Confucian work dynamism also have been identified. These values may independently influence preference. To replicate these results in non-Oriental societies, college students from both Canada (an individualistic society) and Nigeria (a collectivist society) were asked to indicate their preferences for using threats, accept the situation, negotiation, mediation, and arbitration procedures. The participants also completed Hui's (1988) Individualism-Collectivism Scale (INDCOL).
The outcomes did not support the previous research. Canadian subjects showed a stronger preference for negotiation and mediation than Nigerian subjects who, in addition to indicating a greater tolerance for threats, also tended towards arbitration. The INDCOL results also were unexpected; relative to the Nigerian subjects, Canadian subjects were collectivist on the parent and coworker subscales while Nigerian subjects were collectivist on the neighbour subscale. Because the scenarios in the first study were constructed without anticipating that certain domains of individualism and collectivism could exist within the same culture, interpretation of the above results became problematic.
This problem was addressed in two subsequent studies which compared Canadian and Nigerian students on the three domains of individualism-collectivism in which they differed. To this end, Canadian and Nigerian subjects were asked to indicate their preference for methods of resolving a parent-child dispute, a dispute between neighbours, and a third dispute between coworkers. Because Canadians had been found to be more collectivist on the parent and coworker subscales, it was hypothesized that they would prefer negotiation and mediation over arbitration in resolving these conflicts while Nigerians would prefer to use arbitration in the same situation. Conversely, Nigerian subjects were expected to show greater willingness to use negotiation and mediation in resolving a conflict involving neighbours and Canadian subjects were expected to be more inclined toward arbitration. A subsidiary interest was to investigate whether or not people prefer to use different procedures in resolving interpersonal than in resolving intergroup conflicts.
The major hypotheses were confirmed. Canadians were more willing than Nigerians to use negotiation in the parent-child and coworker conflicts while Nigerians showed a greater willingness to use arbitration in both situations. The contradictory finding was the higher ratings by Nigerians on mediation in the parent-child conflict. In the neighbour conflict, Nigerians were more willing to use negotiation while Canadians were more willing to use arbitration. Furthermore, when subjects were divided into high and low scorers on the parent subscale (culture/nationality ignored), a similar pattern of results as described above was obtained.
The analysis of the type of conflict variable revealed that arbitration is preferred to a greater extent in resolving intergroup than interpersonal conflicts. Implications of these findings for the theory of procedural preference and practice of conflict processing are discussed.
Keywords: Psychology; Psychology